Global burden and future trends of inguinal, femoral, and abdominal hernia in older adults: A systematic analysis from the Global Burden of Disease Study 2021 - Jinwei Zhang; Jiaxuan Wang; Xiangyu Han; Junjie Fan; Chao Huang; Yonghong Dong (PLoS ONE, 2025)
Objective This study aims to comprehensively evaluate the global, regional, and national burden, trends, and health inequalities of inguinal, femoral, and abdominal hernias among older adults from 1990 to 2021, conduct predictive analyses, and provide insights to inform future public health strategies. Methods A secondary analysis was conducted using the Global Burden of Disease 2021, focusing on the temporal trends, health inequality, and predictive development of inguinal, femoral, and abdominal hernia burden among older adults. Results Globally, the number of incident cases of inguinal, femoral, and abdominal hernias among older adults continuously increased from 1990 to 2021, along with the decline in age-standardized rates, prevalence, and Disability-Adjusted Life Years (DALYs). Older males exhibited higher incidence rates, prevalence, and DALYs for hernias relative to females. In terms of the Socio-Demographic Index (SDI) from 1990 to 2021, the Age-Standardized Prevalence Rate (ASPR) and Age-Standardized Rate of Disability-Adjusted Life Years (ASDR) remained the highest in low-middle and low SDI regions, while the Age-Standardized Incidence Rate (ASIR) was the highest in high SDI regions. At the national level, 10 countries experienced a significant increase in ASDR and ASPR, and 15 countries in ASIR. Among these, the highest increase was observed for ASIR in China, ASPR in Georgia, and ASDR in American Samoa. The projections to the year 2035 indicate an increase in the incidence and prevalence of hernias, with older males remaining predominant. However, the DALY rate is expected a declining trend. Conclusions In spite of the progress in reducing the burden of inguinal, femoral, and abdominal hernias in older adults, the overall burden tends to rise. In particular, countries such as India, China, and Georgia are experiencing an increasing burden. It is crucial to implement targeted medical interventions, especially for older males in these regions.